2022
DOI: 10.2147/cmar.s389591
|View full text |Cite
|
Sign up to set email alerts
|

The Chemoprotective Role of Vitamin D in Skin Cancer: A Systematic Review

Abstract: Introduction Research in mice showed that vitamin D receptor deficiency was correlated with an increased rate of non-melanoma skin cancer. Therapeutic supplemental vitamin D has also been reported to reduce cell growth in both melanoma and non-melanoma skin cancer. This paper aims to describe the existing research studies that discuss the potential and role of vitamin D in the management of skin cancer. Methods Articles were searched from three databases (PubMed, Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The mechanisms involved include elevating the levels of anti-inflammatory cytokines while lowering the levels of proinflammatory cytokines. It is also indicated as a therapeutic option in the management of diabetes mellitus [ 160 , 161 ] and skin diseases [ 162 ]. Cheng et al [ 163 ] conducted a systematic review and randomized control trial and observed that vitamin D can reduce negative emotions.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms involved include elevating the levels of anti-inflammatory cytokines while lowering the levels of proinflammatory cytokines. It is also indicated as a therapeutic option in the management of diabetes mellitus [ 160 , 161 ] and skin diseases [ 162 ]. Cheng et al [ 163 ] conducted a systematic review and randomized control trial and observed that vitamin D can reduce negative emotions.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search yielded a total of 269 relevant articles. Ten SRs fulfilled our eligibility criteria and were included in the review, with 7 of those conducting meta-analysis of the data [13,14,[22][23][24][25][26][27][28][29]. The study selection process is depicted by the flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Six of these studies directly investigated the association of Vit D and NMSC, mainly in Europe and the USA, one study investigated VitD and BCC formation while another study focused on several types of cancer including NMSC. The remaining two examined the chemoprotective role of VitD on BCC and SCC, with Sutedja et al testing its role in patients with confirmed malignancies [27]. Of note, Abdelwahab et al included 4 studies from Mahamat-Saleh et al in their review [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations